2020
DOI: 10.1108/ijrdm-03-2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in the fashion industry: consumer responses to generative adversarial network (GAN) technology

Abstract: PurposeThis study examines consumers' evaluations of product consumption values, purchase intentions and willingness to pay for fashion products designed using generative adversarial network (GAN), an artificial intelligence technology. This research investigates differences between consumers' evaluations of a GAN-generated product and a non-GAN-generated product and tests whether disclosing the use of GAN technology affects consumers' evaluations.Design/methodology/approachSample products were developed as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…, 2021). For example (Sohn et al. , 2020) applied the five value dimensions of values – functional, social, emotional, epistemic and conditional – to the study of generative adversarial network technology in fashion retailing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021). For example (Sohn et al. , 2020) applied the five value dimensions of values – functional, social, emotional, epistemic and conditional – to the study of generative adversarial network technology in fashion retailing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CVT's five dimensions can be further conceptualized into specific forms to incorporate consumption value in diverse contexts involving food consumption (Choe and Kim, 2018), streaming apps (Oyedele and Simpson, 2018), food delivery apps (Kaur et al, 2021) and mobile app usage (Zolkepli et al, 2021). For example (Sohn et al, 2020) applied the five value dimensions of valuesfunctional, social, emotional, epistemic and conditionalto the study of generative adversarial network technology in fashion retailing. Slack et al (2020) demonstrated that functional value (value for money and performance quality), social value (self-image and social approval) and emotional value drive satisfaction during shopping.…”
Section: Consumption Value Theorymentioning
confidence: 99%
“…GAN and its extended models are unstable for design scheme generation, with low image quality and strong randomness. However, Sohn et al [226] demonstrated that artificial intelligence and GAN enhanced customer satisfaction and freshness. Their results showed the potential of GAN in product design.…”
Section: Product Design Based On Image Datamentioning
confidence: 99%
“…(1) Glue preparation: Mix 10ml of 50xTAE solution with 490ml of ultrapure water, mix evenly, configure into 1xTAE solution, then weigh 31.5g of urea into a beaker, and mix quickly with a glass rod; it can be taken out several times during the period Shake and cool to 50-60°C (the outer bottle body can be rinsed with cold water to achieve rapid cooling), add 3 μL of non-toxic nucleic acid dye, mix well; place the beaker in a water bath, heat at 65°C, and then quickly add 37.5 μL TEMED and 250 μL of 10% ammonium persulfate can be quickly stirred with a glass rod for more than ten seconds (the bottle mouth should not face people during stirring to prevent the liquid from splashing) [17][18].…”
Section: Total Dna Detectionmentioning
confidence: 99%